Application Of Amsillaty Method As An Effort To Understand The Yellow Book Of Ula Class Students At As-Sa’idiyyah Islamic Boarding School 2 Bahrul Ulum Jombang - Nurul Fikri Al Ikhasn; Afif Kholisun Nashoih; Khoirun Nisa’ (Lembaga Institute Development of Social Economic Cociety, 2024)
This research is motivated by the author's interest in the phenomenon of the difficulty of learning to read the yellow book in Islamic boarding schools, so that many students still have difficulty reading the yellow book even though they have been studying for a long time. Therefore, the author is interested in researching one of the Islamic boarding schools in Jombang, namely the As-Sa'idiyyah 2 Bahrul Ulum Islamic Boarding School, which according to the level of information, the success of its students in reading the Yellow Book has been tested and seems short and can even be completed in just a few months. This research uses a qualitative approach and the type of research is a case study. Data collection is through observation and interviews. Data analysis is carried out by reviewing all the data and then drawing conclusions. Checking the validity of the data uses triangulation including source triangulation, method triangulation, and researcher triangulation. The research stages start from the pre-field stage, field work stage, and data analysis stage. The findings of this research show that: 1) Planning the amtsilati method consists of five stages: mapping groups of amsilati students, creating learning targets, preparing teachers, preparing teaching materials and preparing evaluation tools. 2) The implementation of the amtsilati method is carried out in accordance with the procedures determined by KH Taufiqul Hakim as the author of the amtsilati method and there are other lessons that support the successful process of the amtsilati method: bandongan, lalaran, takroran, sorogan, murajaah, deliberation, and homework deposit.